PREPARATION, EVALUATION AND OPTIMIZATION OF SOLID LIPID NANOPARTICLE COMPOSED OF FEMOTIDINE (CAHIERS MAGELLANES-NS, 2024)
Posaconazole, lecithin, and stearic acid were used as excipients in the solvent injection method used to create famotidine-containing nanoparticles. Famotidine showed solubility in methanol and chloroform. The phase separation method and the open capillary method were used to determine its partition coefficient and melting point, respectively. At a maximum wavelength of 286 nm, the UV absorbance measurements of standard solutions with drug doses ranging from 15 to 30 µg/mL in methanol showed linearity.The F4 formulation, which outperformed the other six formulations in terms of drug encapsulation efficiency (80%), was chosen for additional in-vitro drug release investigation and release kinetics research. Over the course of 24 hours, the medication release rate for the F4 formulation was 95%.